TANGGUNG JAWAB NEGARA TERHADAP PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Kalman, Kajagi; Arif Budiman, Eren (CENDERAWASIH CONSTITUTIONAL REVIEW, 2026)
The environment plays a crucial role in human survival and must be protected from damage. The primary responsibility for protecting and maintaining the environment rests with the state to ensure its preservation and sustainability. This article explains the forms and legal basis underlying the state's responsibility for environmental protection and management in Indonesia. Based on Article 28H paragraph (1) and Article 33 paragraph (3) of the 1945 Constitution, the state is obliged to protect the right of every individual to a good and healthy environment. Furthermore, Law Number 32 of 2009 concerning Environmental Protection and Management affirms the government's role in regulating, supervising, enforcing the law, and restoring environmental conditions. However, in practice, this responsibility still faces various challenges, such as weak oversight, weak law enforcement, and minimal public participation. Therefore, political commitment and collaboration between the government, the public, and the private sector are needed to achieve sustainable management.